The Extent of Inclusion of Nutrition and ‎Sports International Standards In Vocational ‎Education Textbooks for Seventh Grade in ‎Jordan - “Ali Saleh”, Reem; Al-Resa’i ‎, Mohammed; Hlalat‎, Khetam (Jordan Journal of Educational Sciences, 2021)
The study aimed to reveal the extent of inclusion of international standards in sports and nutrition in the vocational education textbooks for seventh grade in Jordan. A list of sports and nutrition concepts was prepared in accordance with international standards; the list included (8) domains with (37) items. The results of the study showed that the most important axes of sports and nutrition concepts that are proposed to be included in the vocational education textbooks are (health concepts, impact analysis, access to valid and applicable information, communication between individuals, goals setting, decision-making and practicing health-promoting behaviors). It was found that the sports and nutrition indicators included in the textbooks were (16) indicators out of (37) mentioned in sports and nutrition concepts list, at a rate of (43.2%)